Caracterização das regulações motivacionais para o exercício em pacientes após hospitalização por exacerbação da doença pulmonar obstrutiva crônica: um estudo observacional - Araujo, Gustavo Henrique Guimarães (Universidade Federal de São Carlos, 2024)
Exacerbations of COPD (Chronic Obstructive Pulmonary Disease) represent significant events in the course of the disease, with negative impacts on functionality, levels of physical activity, and anxiety and depression levels. Characterizing and understanding behavioral regulations and basic psychological needs in physical exercise can be useful in structuring more effective and tailored interventions for behavioral change involving physical exercise. Objective: To describe the motivational regulations and basic psychological needs for exercise in individuals after ECOPD. Methods: Twenty-seven individuals were included at the time of hospital discharge due to ECOPD. They were assessed for motivational regulations for physical exercise and fulfillment of basic psychological needs. Information was also obtained on limitations in activities of daily living (ADL) and symptoms of anxiety and depression through the Behavioral Regulation in Exercise Questionnaire-2 (BREQ-2), Basic Psychological Needs in Exercise Scale (BPNES), London Chest Activity of Daily Living (LCADL) questionnaire, Hospital Anxiety and Depression Scale (HADS) respectively, and physical activity levels were obtained using the Activ PALM3® accelerometer. Seven days after hospital discharge, the 6-minute walk test (6MWT) was conducted to evaluate exercise capacity, in addition to obtaining clinical and demographic data from electronic medical records. Descriptive statistics were performed, with normally distributed variables described as mean and standard deviation, and non-normally distributed variables as median and interquartile range. Pearson and Spearman correlations were used according to the normality of the data. Results: The majority of the patients involved were female (n = 18; 66.7%), with the disease severity classified mostly as GOLD III (n = 12; 44.4%). Regarding physical activity, 19 (70.7%) were inactive (< 5000 steps). As the main result, identified regulation was higher in patients, 3 (2 – 3), followed by intrinsic regulation 2 (0.5 – 3). Greater fulfillment of the basic psychological needs of relatedness (3.8 ± 0.9) and competence (3.6 ± 0.9) was observed. Associations were identified between identified regulation and forced expiratory volume in 1s (FEV1 % predicted) (r = 0.409; p = 0.034); self-determination index and CAT (COPD Assessment Test) (r = -0.449; p = 0.019); DASI and identified regulation (r = 0.386; p = 0.047), introjected regulation and intrinsic regulation with anxiety and depression symptoms respectively (r = 0.449; p = 0.019; r = 0.415; p = 0.031). Conclusion: After ECOPD, individuals with COPD demonstrate lower self-determination for physical exercise, even recognizing its benefits and having social support. This low self-determination index may explain the physical inactivity after hospital discharge, with an average step count below 5000. Future studies should focus on interventions based on behavior theories to improve motivation and explore the impact of anxiety and depression on adherence to post-discharge exercise programs.
Characterization of motivational regulations for exercise in patients after hospitalization due to exacerbation of chronic obstructive pulmonary disease: an observational study
Keywords: Autodeterminação; DPOC; Motivação; Exercício; Self-determination; COPD; Motivation; Exercise; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL